“For with God nothing is Impossible”: Reflections on African Initiated Churches’ (AICs) Prophets as African Traditional Religions (ATRs) Fundamentalists - Taringa, Nisbert (Prophets, Profits, and the Bible in Zimbabwe: Festschrift for Aynos Masotcha Moyo, 2013)
The chapter explores what AICs prophets retrieve and use from one of the key African traditional religio cultural fundamentals: religious healing. The chapter argues that prophets and their movements are reactive movements that intend to protect the past in African traditional religions, particularly the beliefs and practices in religious healing. This makes the old more powerful than the new in the paradigm that the prophets use in their healing rituals. AICs prophets are Shona traditional religious fundamentalist championing what is perceived to be one of the fundamentals of Shona faith, namely (i) that the causes of illness are the behaviour of the individual, other human beings and evil supernatural powers and (ii) that the role of the diviner-healer is to locate the source of the misfortune and to identify the failure which needs to be rectified. The paper contends that AICs prophets can therefore be regarded as ATR fundamentalists who have rescued Shona traditional religious healing paradigm from oblivion.
free